Improvements in the obstetric center of a public hospital: a case study of the use of Lean Healthcare tools - Oliveira, Willma Bastos Ribeiro; Guimarães , Camille Pereira; Gonçalves, Maria Clara Sampaio; Araujo, Andressa Clara Barbosa de; Pimentel, Cristiane Agra (Brazilian Journal of Production Engineering, 2024)
The Brazilian health system faces challenges in providing services. Focusing on Lean Healthcare, hospital management seeks improvements in relation to process efficiency and the quality of services provided, reducing waste. The research focuses on analyzing and improving the processes of the Obstetric Center (OC) of a hospital in Feira de Santana, using Lean Healthcare. The study aims to identify waste that affects the length of stay of patients in the OC and propose improvements. The research, classified as descriptive and exploratory, was conducted in a case study format and applied Value Stream Mapping (MFV), to identify waste, classify it and suggest improvements. Waste in patient flow, such as unnecessary waiting and movement, was identified, resulting in proposals for changes in processes and organizational culture. Performance indicators, such as length of stay, were defined to monitor results. It is expected that the proposed improvements, combined with the training of professionals on Lean, will reduce the length of stay in the OC by 37%, improving the efficiency and quality of care. The study highlights the importance of continuous improvement of healthcare processes to ensure a more effective and safe service.